2020
DOI: 10.3390/ijerph17186485
|View full text |Cite
|
Sign up to set email alerts
|

The Post-Coronavirus World in the International Tourism Industry: Application of the Theory of Planned Behavior to Safer Destination Choices in the Case of US Outbound Tourism

Abstract: The tourism industry has been seriously suffering from the coronavirus disease (COVID-19) crisis ever since its outbreak. Given this pandemic situation, the major aim of this study is to develop a conceptual framework that clearly explains the US international tourists’ post-pandemic travel behaviors by expanding the theory of planned behavior (TPB). By utilizing a quantitative process, the TPB was successfully broadened by incorporating the travelers’ perceived knowledge of COVID-19, and it has been deepened … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
217
3
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(252 citation statements)
references
References 45 publications
21
217
3
11
Order By: Relevance
“…Several COVID-19 studies have shown that the perceived knowledge and understanding of the disease is associated with intentions to engage in preventive behavior (23,36,37,43). More specifically, accurate knowledge of COVID-19 is positively associated with attitudes and subjective norms (36), the actual practice of preventive measures (23), and following governmental lockdown implementations (37). Promoting accurate knowledge across the entire population may be a challenge, but one that affords the potential to increase adherence to precautions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several COVID-19 studies have shown that the perceived knowledge and understanding of the disease is associated with intentions to engage in preventive behavior (23,36,37,43). More specifically, accurate knowledge of COVID-19 is positively associated with attitudes and subjective norms (36), the actual practice of preventive measures (23), and following governmental lockdown implementations (37). Promoting accurate knowledge across the entire population may be a challenge, but one that affords the potential to increase adherence to precautions.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the TPB framework, the three core components typically did not moderate each other, which indicates that the relationship between these factors is not interactive. It might be more appropriate to modify the paths within the TPB framework differently and to add other moderating variables: Several studies suggest a causal effect of subjective norm on attitudes, such that people's perceived social pressure from critical others contributes to increasing their attitudes toward specific behaviors (36,47,48). Moreover, Han et al (36) found that psychological risk moderated the association between subjective norm and attitudes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into account that tourism is a part of the service sector where consumers are in the focus of business activity, it is crucial for tourism and hospitality market actors to adjust to the obvious shift in consumer behavior, especially to travel safety considerations and increased interest to domestic destinations (Han et al 2020;. As Sheth (2020) predicts, it is likely that consumers will go back to old habits, but their behavior will stay modified by new regulations and procedures in the way they shop and buy products and services.…”
Section: Covid-19 Pandemic Challenges For Sustainable Tourismmentioning
confidence: 99%
“…The most important changes are the enormous disease-avoidance motive and fastgrowing interest of tourists in all countries in domestic destinations [54], both "close-tohome" ones for short (i.e., weekend) trips, and new ones for longer trips. Potential tourists, realizing the dangers and consequences of a novel coronavirus (COVID-19) disease, are likely to be guided by travel-safety considerations when planning their travels, and are likely to prefer domestic tourism to outbound tourism [55]. At the same time, tourist regions and destinations in which the number of COVID-19 cases (for both locals and tourists) is high, risk losing their attractiveness in the eyes of travelers and face difficulties in attracting new guests in the future due to image deterioration [56].…”
Section: Shift In Consumer Behavior: What Is Important For Tourism?mentioning
confidence: 99%